Teaching photography : tools for the imaging educator - Rand, Glenn (Focal press, 2019)
The photographic community is rife with talented and creative practitioners and artists. But making great photographs does not always translate into an ability to teach effectively. This new edition of Teaching Photography approaches photographic education from a point of view that stresses the how and why of the education. It includes the resources that will inspire new and seasoned teachers to help students expand their technical and aesthetic abilities and techniques, as well as their visual literacy and the way photography fits into the wider world. Fully updated to include the online/hybrid classroom environment, collaborative learning, rubrics, and using digital technology, plus techniques for inspiring conversations and critiques.